REPRESENTATION OF AFRICAN AMERICAN IN GHOSTBUSTERS (2016) MOVIE - Paramuswari, Lentera; Lesmana, Fanny; Budiana, Daniel (Scriptura, 2017)
Discrimination towards African American ethnic is a long drawn issue in America. Leslie Jones, an African American actress, received racist tweets after played a role in Ghostbusters (2016) movies. Ghostbusters (2016) is a film that tells the struggle of a group of scientists and an African American to prove the existence of ghost scientifically. This descriptive qualitative study aims to find out how are the Representation of African American in the Ghostbusters (2016) movie by using semiotic method John Fiske. The results of this study show that the character of African Americans in Ghostbusters (2016) movie is still described as being under the white social class both economically and intelligently. Moreover, Ghostbusters (2016) use African American stereotype characteristics as their comical content. Last, African American role in Ghostbusters (2016) was only as white sidekicks.